Linear programming an aid to academic resource allocation for the U.P. College of Engineering - Silverio, Narciso C. (1974)
A mathematical model of the "optimum" number of students in the eight undergraduate degree programs of the College of Engineering was developed using the Operations Research Methodology. The final model was a Linear programming (LP) model which was arrived at in four stages or models starting with the simplest LP model and progressing to more complex ones. The first model considered only the constraint on the availability of faculty members; the second model considered the constraints on the availability of faculty members, lecture rooms, and laboratory rooms and the constraints on the manpower needs of the country. The most critical laboratory equipment and the number of chairs in a room indirectly entered the constraint by limiting the class size that can be accommodated. The model can be made to do the following: 1. Determine the maximum number of students that should be accepted in each degree program subject to the existing resources; 2. Find the number of students that should be accepted in each degree program to be able to satisfy the manpower needs of the country; 3. pinpoint the critical resources that limit the maximum number of students that can be admitted in each degree program; 4. Indicate how the university can most effectively utilize and allocate its available resources; and 5. Indicate the amount of resources required to satisfy a given number of students. The results and conclusions made in the study apply only to colleges and universities containing the conditions and assumptions given in the model. Care must be taken in applying this model to the whole University of the Philippines System, to a different college or university or to the same college but for a different period of time.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: University of the Philippines (Diliman). College of Engineering; Linear programming